2009
DOI: 10.1186/1471-2407-9-186
|View full text |Cite
|
Sign up to set email alerts
|

Low NKp30, NKp46 and NKG2D expression and reduced cytotoxic activity on NK cells in cervical cancer and precursor lesions

Abstract: BackgroundPersistent high risk HPV infection can lead to cervical cancer, the second most common malignant tumor in women worldwide. NK cells play a crucial role against tumors and virus-infected cells through a fine balance between activating and inhibitory receptors. Expression of triggering receptors NKp30, NKp44, NKp46 and NKG2D on NK cells correlates with cytolytic activity against tumor cells, but these receptors have not been studied in cervical cancer and precursor lesions. The aim of the present work … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
139
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 165 publications
(152 citation statements)
references
References 38 publications
6
139
0
Order By: Relevance
“…In addition, we also found that tumor-associated NK cells had significantly decreased expression of NKG2D, NKp46, perforin, and granzyme B as well as increased expression of the inhibitory receptor NKG2A. The results we have examined in murine tumor-associated NK cells correlate well with human studies which have shown that NK cells from human cervical tumors or non-small cell lung carcinoma (NSCLC) display decreased expression of NKp46 and NKG2D 29,30 . In these studies, tumor NK cells were less cytotoxic and displayed a reduced ability to produce IFN-c.…”
Section: Discussionsupporting
confidence: 73%
“…In addition, we also found that tumor-associated NK cells had significantly decreased expression of NKG2D, NKp46, perforin, and granzyme B as well as increased expression of the inhibitory receptor NKG2A. The results we have examined in murine tumor-associated NK cells correlate well with human studies which have shown that NK cells from human cervical tumors or non-small cell lung carcinoma (NSCLC) display decreased expression of NKp46 and NKG2D 29,30 . In these studies, tumor NK cells were less cytotoxic and displayed a reduced ability to produce IFN-c.…”
Section: Discussionsupporting
confidence: 73%
“…Decreased expression of NKG2D has been observed in most cancer patients, which include breast cancer (BC), lung cancer (LC), colorectal cancer (CRC), cervical cancer (CC), pancreatic cancer (PC), gastric cancer (GC) and HCC. [26][27][28][29][30][31] With disease progression, decreased expression of NKG2D can be correlated with decreased NK cell function, most notably reduced cytotoxicity. The significantly 22,28,[34][35][36] Moreover, these alterations are not limited to activating receptors on NK cells.…”
Section: Nk Receptors In Tumorsmentioning
confidence: 99%
“…[26][27][28][29][30][31] With disease progression, decreased expression of NKG2D can be correlated with decreased NK cell function, most notably reduced cytotoxicity. The significantly 22,28,[34][35][36] Moreover, these alterations are not limited to activating receptors on NK cells. There are several studies that show that NK cell dysfunction is correlated with increased expression of the inhibitory receptor NKG2A and HLA-E. 26,37 Another study provided evidence of a significantly increased level of KIR3DL1-positive NK cells in patients with PC, GC and CRC.…”
Section: Nk Receptors In Tumorsmentioning
confidence: 99%
“…It has been shown that NK cells from cancer patients’ PBMCs have decreased expression of activation receptors and functional defects; 49,50 we thus investigated if entinostat treatment could increase the activation phenotype of these NK cells. PBMCs from seven heavily pretreated metastatic breast cancer patients were treated for 48 hours with a clinically relevant exposure of entinostat or DMSO.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, the fact that NK cells from heavily pretreated breast cancer patients had phenotypic changes after exposure to entinostat similar to healthy donor NK cells was a key novel finding of our study since it has been shown that cancer patients often have dysfunctional NK cells that are lacking an active phenotype. 49,50 …”
Section: Discussionmentioning
confidence: 99%